2018
DOI: 10.1002/anie.201807435
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Metal‐Free Transfer Hydrogenation of Iminoboranes with Ammonia Borane and Amine Boranes

Abstract: The first spontaneous, metal-free, room-temperature hydrogen transfer from ammonia borane to an iminoborane is reported. Mechanistic studies of the reaction indicate a concerted transfer of H and H from donor to acceptor with an activation energy far below those of comparable concerted transfer hydrogenations. This reaction was employed in the syntheses and isolation of new B,N-disubstituted aminoboranes, a comparatively rare subset within the aminoborane family. This successful transfer hydrogenation to a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 46 publications
0
26
0
4
Order By: Relevance
“…[2] Being easy-tohandle hydrogen-storage materials, [3] ammonia borane (AB = H 3 N·BH 3 )a nd amine boranes (R 2 NH·BH 3 )h ave also demonstrated their usefulness in catalytic transfer hydrogenation reactions. [12] Detailed experimental and theoretical studies have shown that, in the case of imines and iminoboranes,t he reaction proceeds via pre-coordination of the protic amine hydrogen to the more electronegative nitrogen atom, followed by concerted delivery of both the protic and hydridic hydrogen atoms to the unsaturated bond, via the six-membered transition state depicted in Figure 1a. [12] Detailed experimental and theoretical studies have shown that, in the case of imines and iminoboranes,t he reaction proceeds via pre-coordination of the protic amine hydrogen to the more electronegative nitrogen atom, followed by concerted delivery of both the protic and hydridic hydrogen atoms to the unsaturated bond, via the six-membered transition state depicted in Figure 1a.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Being easy-tohandle hydrogen-storage materials, [3] ammonia borane (AB = H 3 N·BH 3 )a nd amine boranes (R 2 NH·BH 3 )h ave also demonstrated their usefulness in catalytic transfer hydrogenation reactions. [12] Detailed experimental and theoretical studies have shown that, in the case of imines and iminoboranes,t he reaction proceeds via pre-coordination of the protic amine hydrogen to the more electronegative nitrogen atom, followed by concerted delivery of both the protic and hydridic hydrogen atoms to the unsaturated bond, via the six-membered transition state depicted in Figure 1a. [12] Detailed experimental and theoretical studies have shown that, in the case of imines and iminoboranes,t he reaction proceeds via pre-coordination of the protic amine hydrogen to the more electronegative nitrogen atom, followed by concerted delivery of both the protic and hydridic hydrogen atoms to the unsaturated bond, via the six-membered transition state depicted in Figure 1a.…”
mentioning
confidence: 99%
“…[4] While the majority of these reactions are applied to polar substrates,s uch as imines and ketones, [5] there are several examples of transition-metal-and main-group-catalyzed transfer hydrogenations of apolar N=N, [6] C=C, [7] and CC bonds [8] using AB or dimethylamine borane (DMAB) as the hydrogen source.S pontaneous,u ncatalyzed transfer hydrogenation reactions with AB or DMAB have only been reported for imines, [9] highly polarized olefins, [10] aminoboranes [11] and, most recently,i minoboranes. [9,12] In contrast, the Angewandte Chemie Communications 9783 [9,12] In contrast, the Angewandte Chemie Communications 9783…”
mentioning
confidence: 99%
“…[4] Während die Mehrheit dieser Reaktionen auf polare Substrate wie Imine und Ketone beschränkt ist, [5] gibt es einige wenige Beispiele an Übergangsmetall-und Hauptgruppenelement-katalysiertenT ransferhydrierungen von apolaren N = N-, [6] C = C- [7] und C C-Bindungen, [8] bei denen AB oder Dimethylamminboran (DMAB) als Wasserstoffquelle verwendet wird. Spontane,u nkatalysierte Tr ansferhydrierungen mit AB oder DMAB wurden nur fürI mine, [9] stark polarisierte Olefine, [10] Aminoborane [11] und vor kurzem Iminoborane [12] beobachtet.…”
unclassified
“…[9,12] Im Unterschied dazu verläuft die katalysatorfreie Transferhydrierung von 1,1-Dicyanolefinen über einen stufenweisen Reaktionsmechanismus,b ei dem die polare C=C-Bindung zunächst hydroboriert wird. Daraufhin kommt es zur Bildung eines sechsgliedri-gen Übergangzustands,w oraufhin sowohl der protische als auch der hydridische Wasserstoff in einem konzertierten Mechanismus an die ungesättigte Bindung abgegeben werden (Abbildung 1a).…”
unclassified
See 1 more Smart Citation